Prognostic meaning of tissue inhibitors of matrix metalloproteinases TIMP-1 and TIMP-2 in patients with colorectal cancer - Kostova, Elena; Shubeska Stratrova, Slavica (My University, 2020)
The aim of this study was to analyze TIMP-1 and TIMP-2 serum levels in patients with colorectal cancer (CRC) and to correlate the results with the pathological stage of the disease and outcome in order to evaluate the role of TIMP-1 and TIMP-2 serum levels as prognostic markers. The investigation has been made on 82 patients with operable CRC without distant metastases, who had undergone blood tests in order to determine the TIMP-1 and TIMP-2 serum levels in the following points of time: preoperatively, as well as 3, 6, 9 and 12 months postoperatively. Significant differences were found between serum levels of TIMP-1 and TIMP-2 obtained preoperatively and postoperatively, as well as significant association of serum TIMP-1 levels obtained preoperatively in CRC patients in stage I and III, in the 3th and in the 6th month (p<0.001) postoperatively as defined points of time with the outcome of CRC patients. Serum TIMP-2 levels obtained preoperatively was significantly associated with the outcome of the CRC patients. Analysis of the obtained TIMP-1 and TIMP-2 serum levels in CRC patients showed statistically significant differences with: disease progression, occurrence of liver metastasis, prior to and post chemotherapy treatment. The results derived a conclusion that the serum levels of TIMP-1 and TIMP-2 could be indicators for occurrence and progression of CRC, as well as valuable and useful markers for following the effects of chemotherapy treatment.
Keywords: colorectal cancer; TIMP-1; TIMP-2; prognosis